La responsabilidad social universitaria en Ecuador (Estudios) - Espinoza Santeli, María Genoveva (2017)
This paper of this paper analyzes the theoretical assumptions and practices of university social responsibility (USR) in universities located in Quito Metropolitan District (QMD), to develop a contrast between theory and practice of the RSU and identify the most common behaviors of its management. It starts identifying the universities to be evaluated, a literature review is done. In a second moment, we identify the variables to be used during the survey, interviews and observations. Finally, a comparison between the universities followed.